Strengthening a Sustainable Economy Based on the Green Economy and SDGs through Liquid Organic Fertilizer (POC) Innovation from Household Waste by the Sekarwangi PKK Women - Sari, Dhany Efita; Endang Setyaningsih; Sitti Retno Faridatussalam; Hanifah Tria Intan Jelita; Raden Ahmed Abdillah (Universitas Muhammadiyah Surakarta, 2025)
Household organic waste has emerged as a major environmental issue in Dibal Village, Ngemplak District, Boyolali Regency, since most vegetable, fruit, and leaf residues are simply discarded, causing unpleasant odors and environmental pollution. This challenge is even more pronounced given that among the 74 active members of the “Sekarwangi” PKK women’s group, 27 work as vegetable farmers and market vendors, making them the primary contributors of organic waste in the form of unsold vegetables and fruits. Paradoxically, such waste holds significant potential to be transformed into liquid organic fertilizer (POC), which is both beneficial for home gardening and economically valuable. This community engagement program was designed to provide practical solutions through technical training, the distribution of anaerobic composters, and continuous mentoring for all PKK members. The implementation consisted of five stages: socialization, hands-on training in POC production using bio-activators, distribution of 74 composting units, weekly fermentation monitoring, and evaluation through product trials and satisfaction surveys. The program demonstrated a remarkable behavioral transformation: from merely discarding waste to actively converting it into valuable products. By the reporting period, three harvest cycles had been completed, yielding a total of approximately 124 liters of POC (equivalent to 8 Le Minerale gallons)—far exceeding the initial target of 50 packages. When converted into commercial packaging, the production amounts to 496 bottles of 250 ml (priced at IDR 10,000, potential revenue IDR 4,960,000) or 248 bottles of 500 ml (priced at IDR 20,000, with the same value). Part of the POC has been utilized for household gardening, while the remainder is ready for commercialization as a community product. This program has proven effective in reducing organic waste, fostering awareness of the green economy, and strengthening the community’s economic independence. Recommendations for future action include product and packaging standardization, enhancement of digital marketing strategies, and market expansion through local bazaars or agricultural partnerships to ensure that the economic potential can be sustainably realized, thereby contributing to the achievement of the Sustainable Development Goals (SDGs).